2023
DOI: 10.1172/jci167339
|View full text |Cite
|
Sign up to set email alerts
|

Biological rhythms in COVID-19 vaccine effectiveness in an observational cohort study of 1.5 million patients

Abstract: BACKGROUND Circadian rhythms are evident in basic immune processes, but it is unclear if rhythms exist in clinical endpoints like vaccine protection. Here, we examined associations between COVID-19 vaccination timing and effectiveness. METHODS We retrospectively analyzed a large Israeli cohort with timestamped COVID-19 vaccinations ( n = 1,515,754 patients over 12 years old, 99.2% receiving BNT162b2). Endpoints included COVID-19 breakthrough i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Further, by analyzing breakthrough Coronavirus disease 2019 (COVID-19) infection in 1.5 million patients as a function of time of vaccination, late morning to early afternoon was found to offer better protection than evening vaccination [ 64 ]. The authors of this study were able to construct a continuous efficacy curve over a 12-hour period using EHR data.…”
Section: Opportunities For the Use Of Ehr In Circadian Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Further, by analyzing breakthrough Coronavirus disease 2019 (COVID-19) infection in 1.5 million patients as a function of time of vaccination, late morning to early afternoon was found to offer better protection than evening vaccination [ 64 ]. The authors of this study were able to construct a continuous efficacy curve over a 12-hour period using EHR data.…”
Section: Opportunities For the Use Of Ehr In Circadian Medicinementioning
confidence: 99%
“…Besides pitfalls that pertain to research with EHR in general, the use of these databases for circadian medicine purposes introduces multiple challenges ( Table 1 ). The COVID-19 vaccine timing study [ 64 ] offers a good example. In that study, an individual’s occupation may have independently influenced both the time of vaccination and the risk of COVID-19 infection ( Fig 2A ).…”
Section: Challenges For the Use Of Ehr For Circadian Medicinementioning
confidence: 99%
“…When time of dosing was examined in smaller intervals, the lowest rates of breakthrough infections were found in those vaccinated in the late morning to early afternoon. Interestingly, prior studies looking at time of day of COVID vaccination and subsequent antibody titers have been equivocal ( 2 , 3 ), and this is the first study to our knowledge that included clinical protection as an outcome ( 1 ).…”
mentioning
confidence: 92%
“…In this issue of the JCI , Hazan et al ( 1 ) report on whether time of day of COVID vaccination associates with subsequent breakthrough COVID-19 infection in 1,515,754 patients, using data from a large Israeli health maintenance organization. The authors found evidence to support that the timing of vaccine dosing associated with clinical outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation